(untitled) - Gebhard, Jerry G. (Cambridge, UK, 1999)
This book is a guide devoted to what language teachers can do to become more aware of and explore their teaching beliefs, attitudes, and practices. It provides teachers with the kind of knowledge and guidelines that can empower them to make their own informed teaching decisions. As such, teacher educators will find this a practical book to use in training courses
Keywords: Language and languages; Study and teaching